Analysis and optimization of a tethered wave energy converter in irregular waves - Bachynski, Erin E.; Young, Yin Lu; Yeung, Ronald W. (Renewable energy, 2012)
An understanding of the fundamental system dynamics of wave energy converters (WECs) is required to safely and reliably benefit from the available wave energy resource to produce electricity. The effects of the geometry, mooring system, and mass distribution on the idealized power takeoff of a tethered wave energy absorber in irregular waves are examined. The effects on coupled pitch and sway motions are also considered using a linear frequency-domain method, based on potential flow theory, to obtain the hydrodynamic coefficients. Superposition is used to calculate the response in irregular waves. The objectives of this paper are to examine the characteristic system response of WECs, and to demonstrate the use of an efficient potential-based method for the optimization of a WEC to maximize the annual power takeoff while ensuring system safety at a given site. The analyses suggest that the idealized power takeoff damping increases with the size of the WEC, with the intensity of motion limited. A relatively light mooring system has little effect on the power takeoff, but it introduces a low-frequency coupled pitch-surge resonance that can cause system failure if subject to long-period swells. To mitigate the risk of coupled surge-pitch related failures, a low center of gravity and a low radius of gyration of the floater about the center of floatation are recommended. The results also demonstrate the importance of tuning the system for the site-specific probabilistic wave climate in order to maximize total energy capture and avoid potential failures. ► Fundamental dynamic response of moored wave energy converters in 3 degrees of freedom. ► Semi-analytical method to maximize energy extraction and ensure structural safety. ► Important to tune resonance frequencies to site-specific probabilistic wave climate. ► Mooring lines introduce additional low-frequency resonance. ► Low center of gravity and low radius of gyration minimize coupled pitch-surge motion.